Many-body theory of all-optical quantum well logic gates - Pereira Jr., M.F.; Prado, M.; Sampaio, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
A many-body theory, based on the solutions of generalized semiconductor Maxwell-Bloch equations for coupled-band multiple quantum wells is applied to the description of the optical non linearities responsible for the operation of a resonator as a logical device. The numerical simulation of a NOR gate is in good agreement with experimental realizations.